1992
DOI: 10.4141/cjas92-079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding supplemental fat or lysine during the postweaning period on the reproductive performance of sows with low or high lactation body weight and fat losses

Abstract: Grandhi, R.R. 1992. Effect of feeding supplemental fat or lysine during the postweaning period on the reproductive performance of sows with low or high lactation body weight and fat losses. Can. J. Anim. . The effects of feeding supplemental fat or lysine during the postweaning period on breeding and subsequent reproductive performance were determined in two experiments ofa 2 x 3 factorial design, using 168 Landrace x Yorkshire hrst-parity (exp. 1) and 180 Yorkshire second-parity (exp. 2) sows. At the end of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…A highly significant positive correlation was observed between sow body weight and backfat changes. Grandhi (1992) also reported similar positive correlation between sow body weight and backfat losses during lactation. Sow body weight and backfat at lactation day 1 tended to be negatively correlated with sow weight and backfat changes and feed intake similar to the relationships observed between the gestation weight gains and these traits.…”
Section: Relationship Between Sow and Piglet Performance Traitssupporting
confidence: 55%
See 1 more Smart Citation
“…A highly significant positive correlation was observed between sow body weight and backfat changes. Grandhi (1992) also reported similar positive correlation between sow body weight and backfat losses during lactation. Sow body weight and backfat at lactation day 1 tended to be negatively correlated with sow weight and backfat changes and feed intake similar to the relationships observed between the gestation weight gains and these traits.…”
Section: Relationship Between Sow and Piglet Performance Traitssupporting
confidence: 55%
“…Cette amélioration était généralement plus stable chez les truies sélectionnées sur l'amincissement du lard dorsal. Race, lysine, acide aminé, énergie, truie, lactation Sows with an excessive loss of body weight and backfat during lactation often experience prolonged weaning-tooestrus intervals (King 1987;Yang et al 1989), poor conception and low embryo survival rates (Grandhi 1992) which can reduce the sow productivity. Inadequate nutrition during lactation can also adversely affect sow milk production causing a reduction in piglet weight gains and reduced survival (Aherne and Kirkwood 1985;Cole 1990).…”
mentioning
confidence: 99%
“…During a nutritional deficiency, sows can mobilize body reserves of fat and protein for milk production, but an excess depletion of body reserves can cause delayed estrus (King 1987;Yang et al 1989), poor conception and embryo survival (Grandhi 1992), resulting in reduced sow productivity. Modern lean genotype sows possess a relatively high genetic potential for milk production, and thus require more dietary energy and amino acids than conventional sows to express their potential [National Academy of SciencesNational Research Council (NAS-NRC) 1998].…”
Section: Mots Clésmentioning
confidence: 99%
“…The data were analyzed separately for first-and second-parity sows, using the general linear model procedure of the Statistical Anaiysis System Institute, Inc. (1985 (Grandhi 1992 (Rheaume and Chavez 1989;Grandhi and Ibrahim 1990). Therefore, both the absorption and retention values were approximately the same for these trace minerals.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…They also reported that sows that were given low feed intakes (2.5 vs. 5.0 kg d-') during lactation failed to deposit any body tissue during the postweaning period. Roos et al (1988) (Grandhi 1992 (AOAC 1984), using the Tecator kjeltec system (Fisher Scientific). The feed and feces samples were ashed, whereas freshly thawed urine was digested with nitric and hydrochloric acids and used to determine calcium, phosphorus, magnesium, potassium, manganese, copper and zinc.…”
mentioning
confidence: 99%